Galactic cosmic ray simulation at the NASA Space Radiation Laboratory. (February 2016) - Norbury, John W.; Schimmerling, Walter; Slaba, Tony C.; Azzam, Edouard I.; Badavi, Francis F.; Baiocco, Giorgio; Benton, Eric; Bindi, Veronica; Blakely, Eleanor A.; Blattnig, Steve R.; Boothman, David A.; Borak, Thomas B.; et al.
Abstract: Most accelerator-based space radiation experiments have been performed with single ion beams at fixed energies. However, the space radiation environment consists of a wide variety of ion species with a continuous range of energies. Due to recent developments in beam switching technology implemented at the NASA Space Radiation Laboratory (NSRL) at Brookhaven National Laboratory (BNL), it is now possible to rapidly switch ion species and energies, allowing for the possibility to more realistically simulate the actual radiation environment found in space. The present paper discusses a variety of issues related to implementation of galactic cosmic ray (GCR) simulation at NSRL, especially for experiments in radiobiology. Advantages and disadvantages of different approaches to developing a GCR simulator are presented. In addition, issues common to both GCR simulation and single beam experiments are compared to issues unique to GCR simulation studies. A set of conclusions is presented as well as a discussion of the technical implementation of GCR simulation.